Electron mobility limited by surface and interface roughness scattering in AlxGa1-xN/GaN quantum wells - 王建霞 杨少延 王俊 刘贵鹏 李志伟 李辉杰 金东东 刘祥林 朱勤生 王占国 (中国物理B：英文版, 2013)
The electron mobility limited by the interface and surface roughness scatterings of the two-dimensional electron gas in AlxGa1-xN/GaN quantum wells is studied. The newly proposed surface roughness scattering in the AlGaN/GaN quantum wells becomes effective when an electric field exists in the AlxGa1-xN barrier. For the AlGaN/GaN potential well, the ground subband energy is governed by the spontaneous and the piezoelectric polarization fields which are determined by the barrier and the well thicknesses. The thickness fluctuation of the AlGaN barrier and the GaN well due to the roughnesses cause the local fluctuation of the ground subband energy, which will reduce the 2DEG mobility.